Dextran: Influence of Molecular Weight in Antioxidant Properties and Immunomodulatory Potential - Soeiro, Vinicius C. (Int J Mol Sci, 2016)
Dextrans (α-d-glucans) extracted from Leuconostoc mesenteroides, with molecular weights (M(W)) of 10 (D10), 40 (D40) and 147 (D147) kDa, were evaluated as antioxidant, anticoagulant and immunomodulatory drugs for the first time. None presented anticoagulant activity. As for the antioxidant and immunomodulatory tests, a specific test showed an increase in the dextran activity that was proportional to the increase in molecular weight. In a different assay, however, activity decreased or showed no correlation to the M(W). As an example, the reducing power assay showed that D147 was twice as potent as other dextrans. On the other hand, all three samples showed similar activity (50%) when it came to scavenging the OH radical, whereas only the D10 sample showed sharp activity (50%) when it came to scavenging the superoxide ion. D40 was the single dextran that presented with immunomodulatory features since it stimulated the proliferation (~50%) of murine macrophages (RAW 264.7) and decreased the release of nitric oxide (~40%) by the cells, both in the absence and presence of lipopolysaccharides (LPS). In addition, D40 showed a greater scavenging activity (50%) for the hydrogen peroxide, which caused it to also be the more potent dextran when it came to inhibiting lipid peroxidation (70%). These points toward dextrans with a 40 kDa weight as being ideal for antioxidant and immunomodulatory use. However, future studies with the D40 and other similarly 40 kDa dextrans are underway to confirm this hypothesis.